Heterosis for Grain Yield and its Components in Pearl Millet (Pennisetum glaucum (L.) R. Br.): Heterosis for yield in pearl millet - Sharma, Shravan; Solanki, Kanti Lal; Gupta, P C (Annals of Arid Zone, 2023)
The heterosis study for grain yield and its contributing characters was carried out in among 50 hybrids of pearl millet (Pennisetum glaucum (L.) R. Br.)  through Line x Tester mating design. The analysis of variance showed highly significant mean squares differences among the hybrids for all the characters. The variance due to hybrids, lines, testers and line x tester were also significant for all the characters studied indicating presence of considerable variability among the material studied and existence of overall heterosis for all the characters.  Based on the standard heterosis, five hybrids ICMA JMSA 20073 × RCB-IC 925 S3 19-3-1, ICMA 92777 × H77/833-2, ICMA 843-22 × H77/833-2, ICMA  04999 × H77/833-2 and JMSA 20073 × H77/833-2 were identified superior over best check HHB 67 improved for seed yield per plant along with other desirable characters. Hence, these crosses were considered to be most desirable for grain yield per plant.